1996
DOI: 10.1093/clinids/22.5.813
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Vancomycin, Teicoplanin, Metronidazole, and Fusidic Acid for the Treatment of Clostridium difficile--Associated Diarrhea

Abstract: We conducted a prospective, randomized study to compare the efficacy of oral fusidic acid, oral metronidazole, oral vancomycin, and oral teicoplanin for the treatment of Clostridium difficile-associated diarrhea. Treatment resulted in clinical cure for 94% of the patients who were treated with vancomycin, 96% of those treated with teicoplanin, 93% of those treated with fusidic acid, and 94% of those treated with metronidazole. Clinical symptoms recurred in 16% of patients treated with vancomycin, 7% of those t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
244
1
14

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 454 publications
(265 citation statements)
references
References 23 publications
6
244
1
14
Order By: Relevance
“…Excretion of toxin approximates 13% to 24% at 2 weeks and 6% at 4 weeks after therapy. 26,27 Given that NAAT testing is more sensitive than toxin assays, an interval greater than 4 weeks since last testing should be used for testing with a recurrence.…”
Section: Diagnostic Testingmentioning
confidence: 99%
“…Excretion of toxin approximates 13% to 24% at 2 weeks and 6% at 4 weeks after therapy. 26,27 Given that NAAT testing is more sensitive than toxin assays, an interval greater than 4 weeks since last testing should be used for testing with a recurrence.…”
Section: Diagnostic Testingmentioning
confidence: 99%
“…Patients may still shed C. difficile in their stool after diarrhea resolves. [46][47][48] B. Approaches to minimize CDI transmission from the environment 1.…”
Section: Place Patients With Diarrhea Under Contact Precautions Whilementioning
confidence: 99%
“…Area of controversy: Previous research has demonstrated that asymptomatically colonized patients can be a source of transmission of C. difficile and that patients can remain colonized after symptoms cease. 38,39,[47][48][49] However, asymptomatically colonized patients are less likely than symptomatic patients to contaminate their surrounding environment or serve as a source of transmission. In some settings, the duration of contact precautions can be extended if there is concern that asymptomatically colonized patients represent a significant source of potential C. difficile exposure.…”
Section: Place Patients With Diarrhea Under Contact Precautions Whilementioning
confidence: 99%
“…Antibiotic stewardship is recommended to reduce the risk of CDI. (Strong recommendation, high-quality evidence) 33. Contact precautions for a patient with CDI should be maintained at a minimum until the resolution of diarrhea.…”
mentioning
confidence: 99%